Advanced technology in water management proceedings of the conference organized by the Institution of Civil Engineers and held in London on 27-28 November 1990. (Thomas Telford, 1991)
During the 1980s the water industry made great strides in introducing advanced technology in water management. This book reflects on the achievements made during the last decade and addresses the challenges facing the industry in the 1990s.